(untitled) (The Journal of Plant Protection Sciences, 2021)
The papaya mealybug, Paracoccus marginatus (Williams & Willink) colonize the ventral surface of the papaya leaves along the veins and later disperse to the unripe fruits rendering them unmarketable and inedible. The damage appeared to be in the range between 70 and 95 per cent. Generally young plants die due to heavy infestation and colony formation of the mealybug. P. marginatus is a polyphagous pest attacking several agricultural, horticultural crops, ornamental plants and weeds of economic value. The papaya mealybug feeds on the sap of the plants by inserting its stylets into the epidermis of the leaf as well as into the fruit and stem. In doing so, it injects a toxic substance into the leaves. The result is chlorosis, plant stunting, leaf deformation, early dropping of the leaves and fruits, a heavy accumulation of honeydew and death of the host plants. Heavy infestation is capable of making fruits inedible due to the deposition of thick white waxy material by this mealybug. Five biopesticides i.e., tobacco medicine (100 %), tobacco leaf extract (20 % ), mehgoni seed oil (5 % ), castor seed oil (5 % ) and neem seed oil (5 % ) were used to assess their effects on the mortality of P. marginatus . It is evident that tobacco medicine exerted the best result in terms of control followed by neem seed oil, mehgoni seed oil, castor seed oil and tobacco leaf extract (20 % ).